2020
DOI: 10.1128/mbio.01999-20
|View full text |Cite
|
Sign up to set email alerts
|

Paracoccidioides Genomes Reflect High Levels of Species Divergence and Little Interspecific Gene Flow

Abstract: Paracoccidioides is the causal agent of a systemic mycosis in Latin America. Most of the inference of the evolutionary history of Paracoccidioides has used only a few molecular markers.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 79 publications
(122 reference statements)
1
18
0
1
Order By: Relevance
“…More recently, the genome of 77 strains representing the five species of Paracoccidioides was sequenced using short-read Illumina technology and used for evolutionary analysis. The results reinforced that all Paracoccidioides species are reciprocally monophyletic, and gene flow (or hybridization) between species is infrequent [25,26]. Today, five structural draft genomes of Paracoccidioides isolates (Pb18, Pb03, Pb01, PbCnh and Pb300) have been sequenced, assembled, annotated and deposited in genomic databases.…”
Section: From the First Description Of The Disease To Functional Genomics-112 Years Of Gathered Knowledge A Brazilian Middle West Perspecmentioning
confidence: 76%
“…More recently, the genome of 77 strains representing the five species of Paracoccidioides was sequenced using short-read Illumina technology and used for evolutionary analysis. The results reinforced that all Paracoccidioides species are reciprocally monophyletic, and gene flow (or hybridization) between species is infrequent [25,26]. Today, five structural draft genomes of Paracoccidioides isolates (Pb18, Pb03, Pb01, PbCnh and Pb300) have been sequenced, assembled, annotated and deposited in genomic databases.…”
Section: From the First Description Of The Disease To Functional Genomics-112 Years Of Gathered Knowledge A Brazilian Middle West Perspecmentioning
confidence: 76%
“…The analysis of the GP43 and ARF sequences allowed to observe that the majority of the isolates in the present study presented complete identity or a few nucleotides difference from isolates of S1b type. The predominance of S1b lineage helps explain the high genetic variability found that even with a small number of isolates it was higher than that observed for the isolates from other Brazilian states and Latin American countries where the PCM is endemic [ 11 , 52 , 55 ].…”
Section: Discussionmentioning
confidence: 98%
“…In accordance with the taxonomic evolution, S1/ P . brasiliensis was proposed to be constituted by two lineages, S1a and S1b [ 11 ], which was later endorsed by other authors [ 18 , 52 , 55 ]. The S1b lineage was associated with most isolates of Paracoccidioides spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations